A novel subcutaneous islet transplantation method using a bioabsorbable medical device to facilitate the creation of a highly vascularized transplantation site - Norio Emoto; Takayuki Anazawa; Kei Yamane; Nanae Fujimoto; Takaaki Murakami; Hiroyuki Fujimoto; Cui Jialin; Satoshi Ishida; Kouki Kurahashi; Aya Izuwa; Hang Su; Kenta Inoguchi; et al. (Cell Transplantation)
Subcutaneous transplantation is garnering attention as a potential transplantation site for pluripotent stem cell–derived islet cells to address the shortage of pancreatic islet transplant donors. However, subcutaneous transplantation of cells presents challenges related to angiogenesis, which is necessary for successful islet bioproduction. This study aimed to investigate a novel method for enhancing vascularization at the transplant site and thereby promote islet engraftment using a clinically available bioabsorbable medical device. A nonabsorbable device (agarose) or a bioabsorbable device (collagen–gelatin sheet [CGS]) loaded with basic fibroblast growth factor (bFGF) was implanted subcutaneously in C57BL/6 mice. There were two other groups of mice, one of which was implanted with CGS alone, which acted as a control, and another group that was implanted with bFGF-loaded agarose rods. Subsequently, 200 islets were transplanted into the subcutaneous pre-vascularized sites. An equivalent number of islets was also transplanted into the portal vein (IPTx) to compare transplantation efficacy. Vascularization of the graft site was evaluated before and after transplantation. bFGF significantly enhanced angiogenesis in the CGS mice. The normalization rate of blood glucose levels following islet transplantation in the bFGF-loaded CGS was group comparable to that in the bFGF-loaded agarose rod and IPTx groups. The presence of islets was confirmed using single-photon emission computed tomography (SPECT/CT), histological examination. Furthermore, it was noted that blood glucose levels rapidly increased after graft removal, showing that graft function was crucial to maintain normoglycemia. Importantly, the bFGF-loaded CGS showed a high rate of engraftment. This novel bioabsorbable medical device method exhibited remarkable efficacy in enhancing subcutaneous islet engraftment, potentially paving the way for a more straightforward and less invasive approach for islet cell transplantation in future clinical applications.